OPTIMALISASI PEMBERDAYAAN NARAPIDANA LEMBAGA PERMASYARAKATAN TERBUKA MELALUI LITERASI KEUANGAN - Nina Farliana; Khasan Setiaji; Indri Murniawaty; Hanif Hardianto (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2020)
The Optimalization of Empowerment to Convicted Criminal in the Open Prison through Financial LiteracyAbstract. One of the empowerment of convicted criminals is done by increasing financial literacy. The aims of community service are: empowering convicted criminals class II B Kendal open prison through training financial management system, and give positive contribution by training financial management systems to improve financial literacy. The method of implementing community service activities is carried out by: coordination and mapping needs in prisons, focus group discussions (FGD) and financial literacy workshops, as well as post workshop assistance. The strategic steps of service are: convicted criminals in the prison class II B Kendal is given knowledge about financial literacy, convicted criminals are given training and understanding to develop financial literacy through financial management training, discussion sessions, questions and answers by giving opportunities to convicted criminals and prison management related to financial literacy, simulations implementation of financial literacy through personal and family financial management, as well as assisting and monitoring implementation financial literacy, and evaluating the results of service activities that have been carried out. Convicted criminals the prison class II B Kendal are dominated by elementary and junior high school graduates, who commit violations of the law due to economic needs. This community service program is a solution to overcome the low financial literacy of fostered citizens. The success of this service program is due to the achievement of target participants as well as the achievement of objectives and activity material. People who have good financial literacy are able to make the right decisions in financial management in order to face global challenges based on technological progress.Keywords: Empowerment, convicted criminal, financial literacy.Abstrak. Pemberdayaan narapidana salah satunya dilakukan dengan peningkatan literasi keuangan. Tujuan kegiatan pengabdian ini adalah memberdayakan narapidana lembaga permasyarakatan terbuka kelas II B Kendal melalui pelatihan sistem pengelolaan keuangan, serta memberikan kontribusi positif dengan adanya pelatihan sistem pengelolaan keuangan untuk meningkatkan literasi keuangan. Metode pelaksanaan kegiatan pengabdian dilakukan dengan: koordinasi dan pemetaan kebutuhan di lapas, focus group discussion (FGD) dan workshop literasi keuangan, serta pendampingan pasca workshop. Langkah strategis pengabdian yaitu: narapidana lapas terbuka kelas II B Kendal diberikan pengetahuan tentang literasi keuangan, narapidana diberikan pelatihan dan pemahaman untuk mengembangkan literasi keuangan melalui pelatihan pengelolaan keuangan, yaitu pencatatan keuangan, sesi diskusi dan tanya jawab dengan memberikan kesempatan kepada narapidana dan pengelola lembaga permasyarakatan terkait literasi keuangan, simulasi implementasi literasi keuangan melalui pengelolaan keuangan pribadi dan keluarga, serta melakukan pendampingan dan monitoring kepada narapidana dalam pengimplementasian literasi keuangan, terakhir melakukan evaluasi hasil kegiatan pengabdian yang telah dilakukan. Warga binaan Lapas Terbuka Kelas II B Kendal didominasi oleh lulusan SD dan SMP, yang melakukan pelanggaran hukum karena dorongan kebutuhan ekonomi. Program pengabdian kepada masyarakat ini sebagai solusi mengatasi rendahnya literasi keuangan warga binaan. Keberhasilan program pengabdian ini karena ketercapaian target peserta serta ketercapaian tujuan dan materi kegiatan. Masyarakat yang memiliki literasi keuangan yang baik mampu membuat keputusan yang tepat dalam pengelolaan keuangannya guna menghadapi tantangan global yang berbasis kemajuan teknologi.Kata kunci: Pemberdayaan, narapidana, literasi keuangan